Volume 9: Ocean Renewable Energy 2015
DOI: 10.1115/omae2015-41532
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Wave Energy Converters Extreme Load Analysis

Abstract: Wave energy converter (WEC) devices are designed to sustain the wave-induced loads that they experience during both operational and survival sea states. The extreme values of these forces are often a key cost driver for WEC designs. These extreme loads must be carefully examined during the device design process, and the development of a specific extreme condition modeling method is essential. In this paper, the key findings and recommendations from the extreme conditions modeling workshop hosted by Sandia Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Yu et al [9] applied a similar approach to develop a framework for analyzing WEC extreme design loads. The study included a series of Monte-Carlo-type linear time-domain simulations to determine the sea state at which extreme loads occur and a set of CFD simulations in regular waves with a statistically determined 100-year maximum wave height.…”
Section: Omae2016-54751mentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al [9] applied a similar approach to develop a framework for analyzing WEC extreme design loads. The study included a series of Monte-Carlo-type linear time-domain simulations to determine the sea state at which extreme loads occur and a set of CFD simulations in regular waves with a statistically determined 100-year maximum wave height.…”
Section: Omae2016-54751mentioning
confidence: 99%
“…The method discretizes the time-accurate Navier-Stokes equations of motion over the computational domain and solves the system of linear equations in the time domain. This solver and numerical model were successfully applied previously for a heaving device in extreme regular waves [9]. The numerical settings used in this study are listed in Tab.…”
Section: Urans Simulationsmentioning
confidence: 99%
“…Uncertainty around the offshore reliability includes the uncertainty in determining the extreme wave conditions. For wave energy systems, the largest loads do not always occur in the highest waves [3][4][5], and peak loads may be due to the motion history of the device and certain combinations of wave height and wave period [6]. International standards [7][8][9] suggest the best practices for determining the site-specific environmental conditions and the design load cases for marine structures, such as offshore floating wind platforms, wave energy converters, mooring systems, and offshore oil platforms.…”
Section: Introductionmentioning
confidence: 99%
“…This approach, also commonly referred to as the inverse first-order method (I-FORM), was popularized for ocean systems by Winterstein and Haver [30,31]. Contour analyses have been applied for WECs in multiple studies [29,32] and are suggested for offshore structures in N-003 and DNV-RP-C205. For a desired return period, e.g., 50 years, an environmental contour is determined.…”
Section: Design Frameworkmentioning
confidence: 99%